Sensing the Nation's Law Historical Inquiries into the Aesthetics of Democratic Legitimacy (Studies in the History of Law and Justice, 2018)
This book examines how the nation - and its (fundamental) law - are 'sensed' by way of various aesthetic forms from the age of revolution up until our age of contested democratic legitimacy. Contemporary democratic legitimacy is tied, among other things, to consent, to representation, to the identity of ruler and ruled, and, of course, to legality and the legal forms through which democracy is structured. This book expands the ways in which we can understand and appreciate democratic legitimacy. If (democratic) communities are "imagined" this book suggests that their "rightfulness" must be "sensed" - analogously to the need for justice not only to be done, but to be seen to be done. This book brings together legal, historical and philosophical perspectives on the representation and iconography of the nation in the European, North American and Australian contexts from contributors in law, political science, history, art history and philosophy. .